Хам сэдвээс үгийн утгыг таах: Guessing meaning from contex - O., Gan-Enkh; Ts., Enkhtsetseg (Mongolian Journal of Foreign Languages and Cultures, 2023)
Some teachers of advanced learners of foreign language prefer to expose students to new words in context, hoping students will acquire the vocabulary through contextual clues; whereas others explicitly teach and drill vocabulary. Although the skill of guessing word meanings from context is widely acknowledged as a useful skill, there has been little research in this area and very little useful guidance for teachers or learners. This article focuses on learning of the meanings of new technical words that appear in a written context with explicit clues. The clues involve the following steps: determining the part of speech of the word, looking at the immediate grammar, studying the wider context, and guessing the word and checking the guess. Contextual inference or contextual guessing is defined as an important strategy in the absence of dictionaries or human assistance and it entails guessing the meaning of target word based on interpretation of its immediate context with or without reference to knowledge of the world.